ATLAS b -jet identification performance and efficiency measurement with with t(t)over-bar events in pp collisions at √s=13 TeV - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (The European physical journal. C, Particles and fields, 2019)
The algorithms used by the ATLAS Collaboration during Run 2 of the Large Hadron Collider to identify jets containing b-hadrons are presented. The performance of the algorithms is evaluated in the simulation and the efficiency with which these algorithms identify jets containing b-hadrons is measured in collision data. The measurement uses a likelihood-based method in a sample highly enriched in $$t{\bar{t}}$$tt¯ events. The topology of the → W b$$t→Wb decays is exploited to simultaneously measure both the jet flavour composition of the sample and the efficiency in a transverse momentum range from 20 to 600 GeV. The efficiency measurement is subsequently compared with that predicted by the simulation. The data used in this measurement, corresponding to a total integrated luminosity of 80.5 $$\hbox {fb}^{-1}$$fb-1, were collected in proton-proton collisions during the years 2015-2017 at a centre-of-mass energy $$\sqrt{s}=$$s= 13 TeV. By simultaneously extracting both the efficiency and jet flavour composition, this measurement significantly improves the precision compared to previous results, with uncertainties ranging from 1 to 8% depending on the jet transverse momentum.
Im Titel steht der Buchstabe "s" unter dem Wurzelzeichen
The ATLAS Collaboration: C. Anders, V. Andrei, C. Antel, A. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, L. Herlay [und weitere]
Gesehen am 13.02.2020